Implementation of Islamic Religious Education Learning in Forming Islamic Personal Character - Ardian, Ardian; Habil, Abdul (JUPE : Jurnal Pendidikan Mandala, 2025)
This study discusses the strategies of Islamic religious education teachers in teaching Islamic Religious Education as an effort to shape students' Islamic personalities. This type of research is qualitative research. The interdisciplinary research approach used includes: management, pedagogical, sociological, and psychological approaches. The primary data source of this study is Islamic religious education teachers. Secondary data sources in this study include school profile data, theories on the concept of learning strategies, Islamic religious education theories, and theories of Muslim personality formation. Data collection techniques used observation, interviews, and documentation. Data were analyzed using the stages of data reduction, data presentation, and drawing conclusions. The results of the study found that Islamic religious education learning strategies in shaping students' Muslim personalities use two learning strategies, namely direct learning and indirect learning.